2003
DOI: 10.1149/1.1541255
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Plating of Copper on Metal-Nitride Diffusion Barriers Initiated by Displacement Plating

Abstract: Copper is deposited on TaN and WN barrier layers by electroless plating without the need for activation preprocessing when substrates are ͑i͒ pretreated by wet chemical etching to remove surface oxides, and ͑ii͒ immersed in an electroless Cu plating solution containing glyoxylic acid as a reducing agent. Electrical potential measurements indicate that the redox potentials of TaN and WN in the plating solution are lower than that of copper, driving displacement plating of Cu in the initial stage of deposition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 18 publications
2
48
0
Order By: Relevance
“…Recently, it has been proved that this simple and spontaneous process is an attractive approach for the growth of structures directly on metal or semiconductor substrates such as deposition of Au on Si [2], Ag/Pd on Si [3], Cu on Si [4], Pt on Ti [5], Au on Ge [6], Pt on Ge [7], Cu on TaN [8], Cu on Al [9], Zn on Al [10], Ni on Al [11], Pd on Ag [12], Pt/Au on Cu [13], Au on Cu [14], Ag on Cu [15] and Au on Ag [16] and other combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proved that this simple and spontaneous process is an attractive approach for the growth of structures directly on metal or semiconductor substrates such as deposition of Au on Si [2], Ag/Pd on Si [3], Cu on Si [4], Pt on Ti [5], Au on Ge [6], Pt on Ge [7], Cu on TaN [8], Cu on Al [9], Zn on Al [10], Ni on Al [11], Pd on Ag [12], Pt/Au on Cu [13], Au on Cu [14], Ag on Cu [15] and Au on Ag [16] and other combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, copper electroless plating and chemical vapor deposition ͑CVD͒ are the most promising processes for the formation of a seed layer for electroplating. [5][6][7][8][9] Bottom-up filling of submicrometer features by iodine-catalyzed CVD was reported by Shim et al, 5 Pyo et al,and Josell et al,7 but adhesion between the copper film and barrier metal layer was poor and the deposition rate was slow. Copper electroless plating, which does not require a sputtered Cu seed layer, is an efficient means of filling high-aspect-ratio holes and has became increasingly important.…”
Section: Introductionmentioning
confidence: 96%
“…Copper electroless plating, which does not require a sputtered Cu seed layer, is an efficient means of filling high-aspect-ratio holes and has became increasingly important. 8,9 When the aspect ratio ͑a rate of hole depth to hole diameter͒ is higher than 3, it is difficult for normal electroless plating to fill the high aspect via hole. Recently, we found that a continuous Cu seed layer as thin as 10 nm could be deposited by electroless plating on 1 nm Pd layer formed by the ionized cluster beam ͑ICB͒ and the adhesion between electroless-plated Cu film and TaN barrier layer was good enough to endure chemical mechanical polishing ͑CMP͒.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Furthermore, it is attractive for replacing conventional PVD Cu seed layers in dual-damascene fabrication of Cu interconnects. [15][16][17][18] Recently, we reported a feasibility study for TSV metallization seed layer using Ru as catalytic underlayer for ELD Cu. 10,11 The ELD Cu was deposited inside TSVs along the sidewalls.…”
mentioning
confidence: 99%